Microtubule-destabilizing agents enhance STING-mediated innate immune response via biased mechanism in human monocyte cells - Lim, Songhyun; Jung, Hee Ra; Lee, Hyelim; Chu, Yeonjeong; Kim, Hyejin; Kim, Eunha; Lee, Sanghee (Biomedicine and Pharmacotherapy, 2023)
The stimulator of the interferon gene (STING) signaling pathway acts as a primary defense system against DNA pathogens. Because of the crucial role of STING in type I interferon (IFN) response and innate immunity, extensive research has been conducted to elucidate the roles of various effector molecules involved in STING-mediated signal transduction. However, despite the substantial contribution of microtubules to the immune system, the association between the STING signaling pathway and microtubules remains unclear. In this study, we revealed that the modulation of STING via microtubule-destabilizing agents (MDAs) specifically induced type I IFN responses rather than inflammatory responses in human monocytes. Co-treatment of MDAs with STING agonists induced the elevation of phospho-TANK-binding kinase 1 (TBK1), amplifying the innate immune response. However, during the deficiency of TBK1, the non-canonical signaling pathway through nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) contributed to MDA-induced STING activation in type I IFN response which suggested the versatile regulation of MDA in STING-mediated immunity.
Keywords: Humans; Immunity, Innate; Interferon Type I; Membrane Proteins; Monocytes; NF-kappa B; Signal Transduction; Microtubule; Pro-inflammatory response; Stimulator of interferon genes (STING); Type I interferon response